Changes in Molecular Size Distribution of Cellulose during Attack by White Rot and Brown Rot Fungi - Kleman-Leyer, Karen (1992)
The kinetics of cotton cellulose depolymerization by the brown rot fungus Postia placenta and the white rot fungus Phanerochaete chrysosporium were investigated with solid-state cultures. The degree of polymerization (DP; the average number of glucosyl residues per cellulose molecule) of cellulose removed from soil-block cultures during degradation by P. placenta was first determined viscosimetrically. Changes in molecular size distribution of cellulose attacked by either fungus were then determined by size exclusion chromatography as the tricarbanilate derivative. The first study with P. placenta revealed two phases of depolymerization: a rapid decrease to a DP of approximately 800 and then a slower decrease to a DP of approximately 250. Almost all depolymerization occurred before weight loss. Determination of the molecular size distribution of cellulose during attack by the brown rot fungus revealed single major peaks centered over progressively lower DPs. Cellulose attacked by P. chrysosporium was continuously consumed and showed a different pattern of change in molecular size distribution than cellulose attacked by P. placenta. At first, a broad peak which shifted at a slightly lower average DP appeared, but as attack progressed the peak narrowed and the average DP increased slightly. From these results, it is apparent that the mechanism of cellulose degradation differs fundamentally between brown and white rot fungi, as represented by the species studied here. We conclude that the brown rot fungus cleaved completely through the amorphous regions of the cellulose microfibrils, whereas the white rot fungus attacked the surfaces of the microfibrils, resulting in a progressive erosion.